Gas phase C6H6 - anion: Electronic stabilization by opening of the benzene ring - Pysanenko, Andriy; Vinklárek, Ivo S; Fedor, Juraj; Fárník, Michal; Bergmeister, Stefan; Kostal, Vojtech; Nemirovich, Tatiana; Jungwirth, Pavel (The Journal of chemical physics, 2022)
It is well established that an isolated benzene radical anion is not electronically stable. In the present study, we experimentally show that electron attachment to benzene clusters leads to weak albeit unequivocal occurrence of a C6H6 - moiety. We propose here-based on electronic structure calculation-that this moiety actually corresponds to linear structures formed by the opening of the benzene ring via electron attachment. The cluster environment is essential in this process since it quenches the internal energy released upon ring opening, which in the gas phase leads to further dissociation of this anion.